Bridging integrator 1 protein loss in Alzheimer's disease promotes synaptic tau accumulation and disrupts tau release. Issue 1 (14th February 2020) - Glennon, Elizabeth B; Lau, Dawn H W; Gabriele, Rebecca M C; Taylor, Matthew F; Troakes, Claire; Opie-Martin, Sarah; Elliott, Christina; Killick, Richard; Hanger, Diane P; Perez-Nievas, Beatriz G; Noble, Wendy
Abstract: Polymorphisms associated with BIN1 (bridging integrator 1) confer the second greatest risk for developing late-onset Alzheimer's disease. The biological consequences of this genetic variation are not fully understood; however, BIN1 is a binding partner for tau. Tau is normally a highly soluble cytoplasmic protein, but in Alzheimer's disease, tau is abnormally phosphorylated and accumulates at synapses to exert synaptotoxicity. The purpose of this study was to determine whether alterations in BIN1 and tau in Alzheimer's disease promote the damaging redistribution of tau to synapses, as a mechanism by which BIN1 polymorphisms may increase the risk of developing Alzheimer's disease. We show that BIN1 is lost from the cytoplasmic fraction of Alzheimer's disease cortex, and this is accompanied by the progressive mislocalization of phosphorylated tau to synapses. We confirmed proline 216 in tau as critical for tau interaction with the BIN1-SH3 domain and showed that the phosphorylation of tau disrupts this binding, suggesting that tau phosphorylation in Alzheimer's disease disrupts tau–BIN1 associations. Moreover, we show that BIN1 knockdown in rat primary neurons to mimic BIN1 loss in Alzheimer's disease brain causes the damaging accumulation of phosphorylated tau at synapses and alterations in dendritic spine morphology. We also observed reduced release of tau from neurons upon BIN1 silencing, suggesting that BIN1 loss disrupts the function of extracellular tau. Together, these data indicate that polymorphisms associated with BIN1 that reduce BIN1 protein levels in the brain likely act synergistically with increased tau phosphorylation to increase the risk of Alzheimer's disease by disrupting cytoplasmic tau–BIN1 interactions, promoting the damaging mis-sorting of phosphorylated tau to synapses to alter synapse structure and reducing the release of physiological forms of tau to disrupt tau function. Abstract : Polymorphisms associated with bridging integrator 1 (BIN1) increase the risk of Alzheimer's disease. We show that, in Alzheimer's disease, cortex BIN1 is lost from the cytoplasmic fraction and phosphorylated tau accumulates at synapses. This can be mimicked by BIN1 knockdown in cultured neurons, which also caused disrupted dendritic morphology and tau release. Graphical Abstract: